Long-term efficacy of left bundle branch pacing and biventricular pacing in patients with heart failure complicated with left bundle branch block - Li, Jia; Yi, Hongwei; Han, Jun; Han, Hongwei; Su, Xi (Frontiers in Cardiovascular Medicine, 2024)
Keywords：left bundle branch pacing, biventricular pacing, cardiac resynchronization therapy, heart failure, left bundle branch block Background ： Left bundle branch pacing (LBBP) can physiologically correct complete left bundle branch block (CLBBB), and has become the best alternative to biventricular pacing (BiVP). Objective： To compare the efficacy of LBBP and BiVP in patients with heart failure (HF) complicated with CLBBB. Methods：This was a single-center retrospective study. Patients with HF complicated with CLBBB who underwent successful cardiac resynchronization therapy(CRT) in Wuhan Asian Heart Hospital from June 2018 to June 2023 were enrolled and divided into LBBP group and BiVP group according to the pacing method. The primary endpoints were the absolute increase of left ventricular ejection fraction(LVEF), left ventricular end-diastolic diameter(LVEDD), and echocardiographic response rate.Secondary endpoints were all-cause mortality, heart failure hospitalization(HFH), NT-proBNP, paced QRS duration, pacing threshold, and procedural duration.Results：A total of 120 patients were enrolled in this study, including 60 patients in LBBP group and 60 patients in BiVP group. The median follow-up time was 37±19 months. Compared with BiVP group, LBBP group had a more significant increase in absolute LVEF(ΔLVEF) (14.8±9.9% vs 10.7±9.0%, P=0.02), a more significant reduction in LVEDD (56.9±10.9mm vs 61.1±10.8mm, P=0.03), and a higher echocardiographic super response rate (65% vs 45%, P=0.02). There were no significant differences in all-cause mortality (1.7% vs 10.0%, P=0.11) and HFH (6.7% vs 13.3%, P=0.22). In terms of paced QRS duration (128.7±14.1ms vs 137.5±16.5ms, P=0.002), pacing threshold (0.72±0.21V/0.4ms vs 1.39±0.51V/0.4ms, P<0.001), procedural duration(134.1±32.2min vs 147.7±39.4min, P=0.04) ,the LBBP group was superior to the BiVP group.In nonischemic cardiomyopathy(NICM) patients with HF combined with CLBBB and LVEF≤35%, LBBP is better than BiVP.